Facing climate change: Range dynamics and chromosome diversity in Hedeoma multiflora benth, a South American aromatic - medicinal plant at risk - Peralta, Patricia Angelica; Nores, María Jimena; Bach, Hernán Gerónimo; Robbiati, Federico Omar (Elsevier, 2024)
Climate change could significantly affect the geographic distribution of plant species. Hedeoma multiflora is a vulnerable medicinal and aromatic herb that distributes in the Pampa, Espinal and Chaco biogeographic provinces in austral South America. This integrated approach combines ecological models and cytogenetic evidence to assess the effects of climate change on this species. Species distribution modelling using the Maxent model was implemented under current climatic conditions and three future climate change scenarios, integrating data from three Global Climate Models. The most suitable areas span 68,557 km2, encompassing the Sierras Pampeanas in San Luis and Córdoba provinces, and the Tandilia and Ventania systems in Buenos Aires, Argentina. The primary variables influencing the models include elevation (500 to 2000 m.a.s.l.), annual mean temperature (10 to 17 °C), annual precipitation (500 to 900 mm) and precipitation seasonality (50 to 75%). While the results project an expansion in the potential distribution of the species, heterogeneous patterns of range shifts are predicted across the three mountain systems: expansion in Sierras Pampeanas, march in Ventania and retraction in the Tandilia system. Variations in chromosome numbers within four distinct localities were reported, indicating the presence of polyploidy. This could potentially provide adaptive advantages in response to changing climates. This plant lives in habitats that face human-induced alterations and insufficient area protected coverage, then we propose strategies for both in situ and ex situ conservation of this medicinal species in each area.